Iterative reconstruction of medical phantoms on the computing cluster of EAGLE - S. A. Zolotarev; T. A. Taruat; E. G. Bilenko (Системный анализ и прикладная информатика)
Now one of the most important tasks is development and adaptation of iterative methods for the solution of the superbig rarefied systems of the algebraic equations. The problem of iterative parallel reconstruction of three-dimensional images of industrial facilities leads to such computing tasks. The fact that iterative methods of the solution of computing problems of big dimension are implemented on parallel structures much more effectively, than direct methods of their decision is important.